ASSESSMENT OF GENETIC VARIABILITY IN TEST CROSS HYBRIDS OF MAIZE (Zea mays L.) - T. RAMYA VARDHINI, A. PRASANNA RAJESH , I. SUDHIR KUMAR*; D. RAMESH (The Journal of Research ANGRAU, 2023)
Estimation of genetic parameters viz., genetic variability, heritability and genetic advance as percent of mean of a character helps in the selection of the breeding programme for the development of the particular trait. Analysis of variance recorded highly significant differences for twelve characters among 54 test cross hybrids of maize except for protein content. The magnitude of PCV was higher than the GCV for all the characters studied indicating the role of environment in the expression of these traits. Higher estimates of PCV and GCV were recorded by the trait grain yield (kg ha-1). The character grain yield (kg ha-1) also recorded high heritability associated with high genetic advance as per cent of mean indicating the role of additive gene action, and hence, selection of this trait may be effective. Alternatively, the traits days to anthesis, days to silking, ear length, ear girth, kernel rows per ear, and shelling percentage showed medium heritability with lower genetic gain indicating the predominance of non-additive gene action.